High resolution imaging study of interactions between the 37 kDa/67 kDa laminin receptor and APP, beta-secretase and gamma-secretase in Alzheimer's disease. - Jovanovic, K.; Loos, B.; Da Costa Dias, B.; Penny, C.; Weiss, S.F.T. (Public Library of Science., 2014)
Alzheimer's disease (AD) is the most prevalent form of dementia affecting the elderly. Neurodegeneration is caused by the amyloid beta (Aβ) peptide which is generated from the sequential proteolytic cleavage of the Amyloid Precursor Protein (APP) by the β- and γ- secretases. Previous reports revealed that the 37 kDa/67 kDa laminin receptor (LRP/LR) is involved in APP processing, however, the exact mechanism by which this occurs remains largely unclear. This study sought to assess whether LRP/LR interacted with APP, β- or γ-secretase. Detailed confocal microscopy revealed that LRP/LR showed a strong co-localisation with APP, β- and γ-secretase, respectively, at various sub-cellular locations. Superresolution Structured Illumination Microscopy (SR-SIM) showed that interactions were unlikely between LRP/LR and APP and β-secretase, respectively, while there was strong co-localisation between LRP/LR and γ-secretase at this 80 nm resolution. FRET was further employed to assess the possibility of protein-protein interactions and only an interaction between LRP/LR and γ-secretase was found. FLAG co-immunoprecipitation confirmed these findings as LRP/LR co-immunoprecipitated with γ-secretase, but failed to do so with APP. These findings indicate that LRP/LR exerts its influence on Aβ shedding via a direct interaction with the γ-secretase and possibly an indirect interaction with the β-secretase.
Keywords: amyloid precursor protein; beta secretase; gamma secretase; laminin receptor; amyloid precursor protein; laminin receptor; protein binding; secretase; Alzheimer disease; cellular distribution; confocal microscopy; controlled study; fluorescence resonance energy transfer; human cell; immunoprecipitation; microscopy; protein interaction; superresolution structured illumination microscopy; cell line; chemistry; metabolism; molecular imaging; procedures; protein transport; reporter gene